2020
DOI: 10.1164/rccm.202006-2382st
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Noninvasive Ventilation in Chronic Stable Hypercapnic Chronic Obstructive Pulmonary Disease. An Official American Thoracic Society Clinical Practice Guideline

Abstract: Background: Noninvasive ventilation (NIV) is used for patients with chronic obstructive pulmonary disease (COPD) and chronic hypercapnia. However, evidence for clinical efficacy and optimal management of therapy is limited. Target Audience: Patients with COPD, clinicians who care for them, and policy makers. Methods: We summarized evidence addressing five PICO (patients, intervention, comparator, and outcome) questions. The GRADE (Grading of Recommendations, Assessment, Development, and Evaluation) approach wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
111
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 70 publications
1
111
0
Order By: Relevance
“…Furthermore, a meta-analysis published in 2020 concluded that NIVH reduced hospitalizations in COPD-CRF, but did not find that NIVH reduced mortality [11]. Despite the data demonstrating the effectiveness of NIVH for patients with COPD-CRF, and despite a recently published national practice guideline supporting the use of NIVH in COPD-CRF patients [12], NIVH remains infrequently used in the U.S. According to an estimate from the Department of Health and Human Services, only 47,000 of the estimated 1.6 million adults in the U.S. diagnosed with COPD-CRF received NIVH in 2017, resulting in an approximate 3% utilization rate [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a meta-analysis published in 2020 concluded that NIVH reduced hospitalizations in COPD-CRF, but did not find that NIVH reduced mortality [11]. Despite the data demonstrating the effectiveness of NIVH for patients with COPD-CRF, and despite a recently published national practice guideline supporting the use of NIVH in COPD-CRF patients [12], NIVH remains infrequently used in the U.S. According to an estimate from the Department of Health and Human Services, only 47,000 of the estimated 1.6 million adults in the U.S. diagnosed with COPD-CRF received NIVH in 2017, resulting in an approximate 3% utilization rate [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Two factors may explain this high rate. First, patients may continue to need ventilation at home [96], but this practice has not been developed widely. Recent trials of home NIV for patients surviving an ICU admission suggest important potential benefits [34].…”
Section: New Avenues Of Researchmentioning
confidence: 99%
“…Early nocturnal intervention can possibly delay or alter the progression of respiratory failure. For example, nocturnal non-invasive ventilation (NIV) in hypercapnic COPD patients is the mainstay therapy 50 , and home-initiation of such therapy is becoming practical and safe 51 . In neuromuscular disease, early initiation of nocturnal NIV has been advocated in patients with sleep hypercapnia and daytime normocapnia 52 .…”
Section: Treatment During Sleepmentioning
confidence: 99%